2022
DOI: 10.31703/gesr.2022(vii-i).07
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Impact of Demographic Variables on Science Achievement of 8th and 9th Grade Students

Abstract: Quality of science education is under consideration by educationists and researchers.Achievement in science subjects, as an indicator of the quality of science education, not only determines the students' performance but helps the teachers to evaluate their teaching strategies. This study is an effort to explore the factors related to scientific achievement from a Pakistani perspective. A sample of1149 students from 37 public schools of 8th and 9th grades was taken. Results show that parental qualification and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…Similarly, the findings of our research are consistent with the findings of Alokan & Arijesuyo (2013) who found that academic achievement of secondary Schools learners belonging to urban and rural areas differ significantly whereby mean scores of respondents from urban area were greater (M = 2.64, SD = 1.49) than those belonging to rural areas (M = 2.48, SD =1.33). Our results are also similar to the results of Faisal, Shinwari & Hussain (2017) and Shah, Malik & Akhtar (2020) who found that students belonging to urban and rural areas differed in their academic achievement.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, the findings of our research are consistent with the findings of Alokan & Arijesuyo (2013) who found that academic achievement of secondary Schools learners belonging to urban and rural areas differ significantly whereby mean scores of respondents from urban area were greater (M = 2.64, SD = 1.49) than those belonging to rural areas (M = 2.48, SD =1.33). Our results are also similar to the results of Faisal, Shinwari & Hussain (2017) and Shah, Malik & Akhtar (2020) who found that students belonging to urban and rural areas differed in their academic achievement.…”
Section: Discussionsupporting
confidence: 92%
“…This study found that girls' performance in Science is significantly better than that of boys. The findings are consistent with a plethora of studies undertaken globally (Arora et al, 2012;Global Education Monitoring, 2022;Gonzales et al, 2008;Mullis et al, 2004) and in Pakistan (Saeed et al, 2005;Shah et al, 2020) indicating better performance of girls. The findings are encouraging for the policy makers and practitioners who are constantly striving for gender equality in students' performance.…”
Section: Discussionsupporting
confidence: 89%
“…However, these trends have been subjected to continuous changes with the passage of time, and across various contexts. In other words, the available evidence is inconclusive (Baye & Monseur, 2016;Borgonovi & Han, 2021;Meinck & Brese, 2019;TIMSS, 2019), sometimes revealing no differences in academic achievement (Ajai & Imoko, 2015;Bessudnov & Makarov, 2015;Erturan & Jansen, 2015;Sarouphim & Chartouny, 2016;Tsui, 2007), favouring girls in Science and/or Mathematics (Arora et al, 2012;Global Education Monitoring, 2022;Gonzales et al, 2008;Mullis et al, 2004;Saeed et al, 2005;Shah et al, 2020) or demonstrating boys' better performance in Science and/or Mathematics (Asante, 2010;Edgerton et al, 2012;Kumar & Choudhury, 2022;Lau & Lam, 2017;Reilly et al, 2015;Reilly et al, 2019). Scholars have attempted to consolidate the existing literature through meta-analysis in order to generate a comprehensive understanding of gender differences.…”
Section: Trends Of Students' Performance In Science and Mathematicsmentioning
confidence: 99%
See 1 more Smart Citation